Experimental study of simultaneous transmission of ultrasonic waves and optical radiation via optical fiber couplers - Sylwia MUC; Tadeusz GUDRA; Elżbieta BEREŚ-PAWLIK (Archives of Acoustics)
This article presents the results of experimental studies of simultaneous transmission of ultrasonic waves and laser signals in optical fibers by the use of both the optical single mode and multimode fiber couplers. This work was aimed, among other things, at the study of the way the acoustic energy affects a laser beam. The light wave was guided into one of the coupler's arms. The optical power applied to one input of the coupler is separated into two coupler outputs according to the rate determined by the coupling coefficient. Only an ultrasonic wave generated by a sandwich type transducer is applied to the other arm of the coupler. In this experiment, as in case of the light wave, the acoustic power is separated into both the outputs. One can observe the interaction of both the waves on the two outputs - a modulation of the light wave by means of the ultrasonic wave is possible. The output signal was detected using a PIN diode and an optical power meter (OPM). Temporary courses were observed on an oscilloscope screen. The simultaneous transmission of ultrasounds and optical radiation in optical fibers can be used in the construction of medical equipment.